2004
DOI: 10.1037/0096-3445.133.1.101
|View full text |Cite
|
Sign up to set email alerts
|

The Relations Among Inhibition and Interference Control Functions: A Latent-Variable Analysis.

Abstract: This study used data from 220 adults to examine the relations among 3 inhibition-related functions. Confirmatory factor analysis suggested that Prepotent Response Inhibition and Resistance to Distractor Interference were closely related, but both were unrelated to Resistance to Proactive Interference. Structural equation modeling, which combined Prepotent Response Inhibition and Resistance to Distractor Interference into a single latent variable, indicated that 1 aspect of random number generation performance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

114
2,015
22
91

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,906 publications
(2,322 citation statements)
references
References 134 publications
114
2,015
22
91
Order By: Relevance
“…For example, Nigg (2000) distinguished inhibitory control over cognitive processes from inhibitory control over motor responses. In contrast, Friedman and Miyake (2004) found differences between tasks where interference resulted from conflicting information present in the environment within a given trial (i.e., distractor interference) and tasks where interference built up over successive trials (i.e., proactive interference). The second and third models tested, then, grouped the inhibition tasks on the basis of inhibition type (motor vs. cognitive inhibition), and source of interference (distractor interference vs. proactive interference).…”
Section: Models Of Executive Controlmentioning
confidence: 80%
“…For example, Nigg (2000) distinguished inhibitory control over cognitive processes from inhibitory control over motor responses. In contrast, Friedman and Miyake (2004) found differences between tasks where interference resulted from conflicting information present in the environment within a given trial (i.e., distractor interference) and tasks where interference built up over successive trials (i.e., proactive interference). The second and third models tested, then, grouped the inhibition tasks on the basis of inhibition type (motor vs. cognitive inhibition), and source of interference (distractor interference vs. proactive interference).…”
Section: Models Of Executive Controlmentioning
confidence: 80%
“…Sylvester et al (2003) have previously shown that inhibitory control activates both unique and shared (with other cognitive processes such as task switching) cortical regions, with the current study suggesting that the unique regions identified by Sylvester in premotor and prefrontal areas were those called upon during competing demands for common regions. It remains to be seen whether this result can be generalized to other paradigms, for example, recent literature examining inhibition has suggested that the cognitive processes required for Go/Nogo and Stroop-type tasks can be distinguished from those for reducing proactive interference (Friedman and Miyake, 2004). There also remains the possibility that these different forms of inhibition have cortical substrates that interact differently with demands such as increasing WM load (Kok, 1999;West et al, 2002).…”
Section: Common Resourcesmentioning
confidence: 96%
“…Inhibition has received labels such as "interference" (Piai et al 2012) and "suppression" (Ludowig et al 2010) to highlight its automatic nature (implicit or unintentional inhibitory processes) and controlled nature (explicit or intentional inhibitory processes), respectively (Nigg 2000;Friedman and Miyake 2004;Andres et al 2008;Collette et al 2009). This theoretical construct of the level of control that is needed in a cognitive process, in this case inhibition, was initially proposed by Shiffrin and colleagues (for a review, see Shiffrin and Schneider 1977).…”
Section: Theoretical Issues In Inhibitionmentioning
confidence: 99%